Pulsed laser-scanning laser Doppler vibrometer (PL-SLDV) phased arrays for damage detection in aluminum plates - Tian, Zhenhua; Howden, Stephen; Ma, Zhaoyun; Xiao, Wenfeng; Yu, Lingyu (Mechanical systems and signal processing, 2019)
•Fully noncontact Lamb wave phased arrays based on a pulse laser-scanning laser Doppler vibrometer sensing system.•An improved delay-and-sum (DAS) phased array imaging algorithm with better radial and angular resolutions.•Experimental demonstration of detection and localization of various defects on an aluminum plate. Lamb wave phased arrays employ sensors placed close to each other in compact distributions and can quickly inspect large plate-like structures through time (or phase) delays in the way analogous to radar. Traditional Lamb wave phased arrays usually adopt large-size ultrasonic transducers bonded on (or placed close to the surface of) a structure, and hence they limit the array configurability and cannot perform inspection from a far distance to the structure. This paper presents Lamb wave phased arrays implemented with a fully noncontact pulsed laser – scanning laser Doppler vibrometer (PL-SLDV) system, which employs a PL for exciting Lamb waves at a single PL spot through the thermoelastic effect and an SLDV for acquiring signals of Lamb waves at multiple scanning points based on the Doppler effect, respectively. The fully noncontact PL-SLDV phased arrays enable inspection from a far distance, as well as easily constructible receiver phased arrays in various configurations due to the use of high-resolution scanning laser. To generate inspection images with the acquired signals of Lamb waves, an improved delay-and-sum (DAS) imaging algorithm for receiver phased arrays is developed, where the exact Lamb wave frequency-wavenumber dispersion relation is considered for both the phase delay and back-propagation phase. This improved DAS imaging algorithm addresses the dispersion effect and results in higher radial imaging resolution, compared to the conventional DAS imaging algorithm. In addition, adaptive weighting factors are implemented to improve the angular imaging resolution. Proof-of-concept experiments demonstrate that multiple simulated defects of different sizes as well as broadside and offside simulated cracks can be successfully detected using a PL-SLDV phased array with a high-dispersion A0 mode. The experimental study also shows that the improved DAS imaging algorithm can achieve high radial and angular imaging resolution.